ANALISIS BREAK EVEN POINT SEBAGAI ALAT BANTU MANAJEMEN DALAM PERENCANAAN LABA PADA PT. MANDOM INDONESIA, Tbk. PERIODE 2017-2021 - Logika Bago (Universitas Nias Raya, 2022)
The purpose of this study is to determine the sales value that must be achieved so that the company does not experience losses and the application of break even point analysis as a profit planning tool for PT Mandom Indonesia Tbk in 2023-2027. This research is a qualitative research with a descriptive approach by presenting a summary of the data and values ​​calculated based on data obtained from the Indonesian stock exchange. The results of this study show that the largest break even point value occurred in 2018 of Rp. 1,240,490,995,185, with a margin of safety of 53.16%, while the smallest even point of defecation occurred in 2021 of Rp. 683,404,190,643 with a margin of safety of 63 .56%. Based on PT Mandom Indonesia Tbk's profit planning calculations for 2023, a profit of IDR 517,533,753,576 can be obtained from planned sales of IDR 2,882,268,491,403. In 2024 it will earn a profit of IDR 409,280,347,919 from budgeted sales of IDR 3,158,294,641,514 In 2025 it will earn a profit of IDR 301,026,942,262 from budgeted sales of IDR 2,426,040,166,756. In 2026 the company will earn a profit of IDR 192,773,536,605 with budgeted sales of IDR 1,455,687,725,324. PT Mandom Indonesia Tbk is expected to be able to maintain the company's sales value so that it does not touch the margin of safety or safe limits and also the company's sales value is expected to be above the break even point value so that the company avoids losses